The mediating effect of stress and anxiety in the relationship between workplace bullying and intention to leave - Lai, Pei Zhi (2019)
The main goal of the present study is to examine the potential mediating effect of stress and anxiety on the relationship between workplace bullying and intention to leave. Workplace bullying is constantly related to negative outcomes on the victims. Several studies had shown that workplace bullying is prevalent in Malaysia‟s working culture. Even though, many studies had look into the relationship between workplace bullying and intention to leave, little is known about the potential mechanisms of this relationship. A cross-sectional survey design was used in this study. All data was gathered using a self-report questionnaire. The inclusion criteria were individuals who were currently working in Malaysia with a minimum of one year full-time working experience. The results showed that all variables were positively correlated with each other. In the mediation analysis using PROCESS SPSS macro, it was found that workplace bullying has an indirect effect on intention to leave through stress, but not through anxiety. An additional mediation analysis was conducted on both stress and anxiety separately. Surprisingly, the result showed that workplace bullying has an indirect effect on intention to leave through both stress and anxiety. This showed that stress may be a stronger mediator than anxiety, which results in anxiety becoming insignificant when the mediation analysis was conducted concurrently. The present study highlighted that preventive measures must be taken in the very first place to reduce workplace bullying. The result suggests that organizations could consider organizing stress reduction workshops as an alternative to help employees overcome the detrimental effect of bullying when the preventive measures took place.